ONTOLOGY OF THE UKRAINIAN WRITER-EXILE IN MEMOIRS BY ULAS SAMCHUK “FIVE PAST ELEVEN: NOTES AT A RUN” - Podvyshennyi, Alexander (Літературний процес: методологія, імена, тенденції, 2019)
The article analyses the little-studied part of the prose legacy of Ulas Samchuk — a book of memoirs ‘Five past twelve: notes at a run’. Ontological approach to the text allowes to outline the world-wide changes of the writer in the conditions of war and dehumanization of society. With the help of the imagology method, the peculiarities of Ulas Samchuk’s attempt to understand the Other (German) who became a victim of Nazi ideology, tolerance of racial superiority, but ultimately defeated. The writer relies on Western European philosophy, in particular, the ideas of O. Spengler, K. Jaspers, J. Ortega y Gasset, which refers to the decline of western culture in connection with the development of civilization, which seeks for hegemony over mankind. An important role is devoted to reflections on the role and place of the Ukrainian nation in the transcendental epic of redistribution of the world. DOI: https://doi.org/10.28925/2412-2475.2019.1321